Os trabalhadores da cana sob múltiplos olhares: instituições, narrativas e interpretações. Centralina e Araporã - MG (1980-2009) - Resende, Renata Carolina (2011)
The paper CAPES funded for two years investigates in Centralina and Araporã conditions experienced by workers cutting cane, their expectations when they leave their places of origin, the relationship forged with city dwellers, the ways of survival in these small towns, the borrowings and adaptations in these places and as printed in these dynamic areas. It seeks to understand where the plot takes place promised eldorado drafted in 1980 as it was received by the people, both residents of the municipalities and the works who come seeking employment as an agricultural development and uneven places the small producers and farmer s relatives working in the cane fields. From this plot we seek to comprehend how the cane works interpret their work and life trajectory. Through its narrative is understood as the workrs in this process has its category highlighting their ways of living, housing, food, fun and withstand a dynamic balance that defines the universe of work in the cane today.